PENGARUH PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN TANAMAN KANGKUNG(Ipomoea reptans Poir) - Linda Noviana; Ira Mulyawati; Romanna Romanna (Universitas Pahlawan Tuanku Tambusai, 2022)
Indonesia has high biodiversity sources which are now widely used as food ingredients such as vegetables, where it has a very high dependence on nature with our daily lives, so this study discusses environmentally friendly-based agricultural models. The purpose of this study was to find out the effect of applying liquid organic fertilizer with soil control in terms of soil quality, namely soil fertility parameters (pH, N, P, and K). This type of research is an experimental laboratory scale using quantitative descriptive methods. Data analysis used a Randomized Block Design (RAK) and Analysis of Variance (ANOVA) test, then continued with the 5% BNJ test. The compositions used in this study were soil control (without fertilizer) and Liquid Organic Fertilizer (POC). Experimental research was conducted after the age of 15 days after planting (DAT). The results of research on plant physical parameters consisting of plant height (cm) in the ANOVA table show non-significant notation (NS) or it can be said that Fcount >1% and 5%, on the number of leaves (strands) in the ANOVA table shows the notation (**) at treatment which means Fcount > 1% (very significantly different). The treatment category on ANOVA leaf count was further tested by 5% BNJ and showed that X0 (0ml) and X3 (3.4ml) treatments were not significantly different, but significantly different from X1 (1.8 ml) and X2 (2.6 ml) treatments. where X2 is the recommended dose. The parameter test of soil fertility analysis had a normal average pH of 7 in each treatment, consisting of control soil (0 ml) was 6.5, at X1 (1.8 ml) was 7, at X2 (2.6 ml) ) is 7, and X3 (3.4 ml) is 7.2. For testing on Parameters N(Nitrogen), P(Phosphorus), K (Potassium) only tested for soil control only. Keywords : Liquid Organic Fertilizer, Soil Control, Water spinach, ANOVA, Plant Physical Parameters, and Soil Fertility.